Assessment of Hearing in Children with Cerebral Palsy - Gavkhar Khaydarova1, Aziza Madrimova2, Khalida Shaykhova3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The objective of this study is to identify the prevalence and nature of auditory analyzerpathology in children with different forms of infant cerebral palsy by recording otoacoustic emission andrecording short latency brainstem auditory evoked potentials.Materials and Method: The subject group consisted of 75 children, 40 (53%) males and 35 (47%) werefemales, ranging from 3 to 14 years of age with a confirmed diagnosis of cerebral palsy on the basis of apsycho-neurological hospital in Tashkent. (Uzbekistan). The examination of children was carried out bythe following method: clinical examination of patients (general and otorhinolaryngological) and functionalresearch method of the auditory analyzer.Results: All children underwent acoustic impedancemetry, including tympanometry with determination ofthe type of tympanogram and acoustic reflex. The data obtained revealed a bilateral lesion of the peripheralpart of the auditory analyzer. Beilateral sensorineural hearing loss was detected in 21-I-II degree, in 12-III degree and in 15-IV degree. Marked changes in the main parameters of BAEP were detected in thestudy of the stem structures of the auditory analyzer in children with cerebral palsy. Thus, disorganization,configuration disturbances of the component composition (I, III, V) were noted.Conclusion: Thus, the study revealed a disorder of auditory function by sound-detecting type and justifiedthe need for hearing correction in these children. Evaluation of auditory function made it possible todetermine the level of auditory analyzer injury and localization of the process from the results of a complex,objective examination.